Preparation of pomegranate jellies - Maestre J.; Senabre R.; Melgarejo P.; García-Viguera C. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The production of processed foods derived from pomegranate juice is of essential interest, due to the possibility of giving an alternative use to this crop, which is generally consumed fresh. This would provide substantial benefits to the growers. One of these new products that we have assayed, is pomegranate jelly. In order to manufacture this food different jellifying agents were analysed, Agar rendering the best results. Once this objective was fulfilled and the production optimised, the influence of different parameters such as pH and storage temperature were investigated. The main objective of this work was focused on establishing the optimum conditions for obtaining a product with a stable colour, since it is well known that colour is one of the most important quality factors for consumers.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)